Comparative Study on Histopatological and Histomorphometric Effect of Raw and Cooked Garlic on Spermatogenesis in Testis and Epidydims of Rats - khadijeh bahrami; amer Mahjoor; habeballa . gohary; reza bahrami; alireza bahrami (Fasa University of Medical Sciences, 2013)
Background ;Objective: The present study aims at studying two forms of raw and cooked garlic to identify the effect of this plant on the amount of change in histopatological of spermatogenesis of wistar rat.Materials & Methods: 40 male rats were divided into five equal groups (4 treatment 1 control group) the first and second treatment were received palete food consisted of 5% and 15% of raw garlic every day. The third and fourth reatment were received palete food consisted of 5%and 15% of cooked garlic as a food . The control group received standard palete food every day in a month. Finally,the testis were taken out of stomach and after preparing tissue and coloring, they were gone under microscopic studies. Thence, the data were analyzed using SPSS and Duncan test.Results: The study indicated that the amount of sexual cells in the group having cook garlic for 15% compared with that of controlled group had a significant increase and the amount of sexual cells in the group using raw garlic as a food had a significant decrease compared with that of the controlled group.Conclusion: Prescription of cooked garlic has an influence on Proliferation of sexual cells in testicular tubules and epidydymes and so increased spermatogenesis in this group in caparison with the control group. However, prescribing raw garlic has harmful effects on tissue of testis and process of spermatogenes in empric compared with the control group.